EFFECT OF LEAD AND CADMIUM ON IMMUNITY OF TWO VACCINES - H. AL-Attia, H.; A. Khalifa, K.; H. Al-Bayyati‎, S.; P. Ridha, Y.; Al-Khshali, Abdlhusin (The Iraqi Journal of Veterinary Medicine, 1987)
This study was performed to investigate the effect of lead exposure on resistance of mice immunized against haemorrhagic septicaemia and challenged with virulent organisms. Lead treated mice showed greater susceptibility to challenge with P. multucida than control especially if lead nitrate is administered orally. this result showed that treatment with lead initials resistance of mice and might interferes with the vaccination programs. Cadmium chloride (cd) injected into rabbits at various time intervals in relation to tetanus toxoid injection was found to have some effect on the immune response. A reduction in the primary immune response was detected in case if (cd) is given two weeks prior to toxoid injection. On the other hand, enhancement of secondary antibody titers was detected. Cadmium reduced both primary and secondary antibody response if it is given seven days before immunization.